Dominion: architecture as a symbol of authority in the Eastern Cape Colonial Frontier - Mnyila, Desmond (Rhodes University, Faculty of Humanities, Department of Fine Art, 2016)
My mini thesis is an exploration of architecture as part of the landscape of Grahamstown and how ideas of dominion and subordination of the non- white citizens of this town were asserted or communicated through space. I concur with theories about architectural buildings as objects that express power and reinforce power relations in any given society. Markus (1993) goes into great lengths to explain how buildings are primarily about power and town planning is a means of control. The area under consideration is very rich in history especially during the period that interested me which is the nineteenth century as this was a period of the establishment of Grahamstown, firstly, as a military establishment and then as a small town serving as a residential area for the British Settlers who arrived in 1820. Throughout the mini thesis I have unpacked the nature of power itself by referring to Njoh (2009) who refers to different categories of the use and especially the abuse or demonstration of power. It wouldn't do justice to an area as rich in history as the area which is now referred to as the Albany to not dwell into some of the events that were played out here, some of which had consequences and implications for the rest of South Africa. After 1820, the town developed as more buildings of domestic houses, churches, houses of officials, prisons and schools were built. In the thesis I unpack the different architectural styles like the Georgian, Victorian and Cape Dutch styles that formed a significant part of this small town. I draw attention to the ideas of dominion that Njoh elucidates, which were played out in the building of the town architectural structures. Architecture demonstrated British might and power through the imposition of British and European architectural styles on an African landscape. The sheer magnitude of the buildings, I argue, was carefully planned and the use of durable materials, often stones that were imported from abroad, was a carefully orchestrated move to demonstrate British wealth and power through intimidation and seduction. Thomas Baines was one of the artists who spent some time in Grahamstown and made a series of the landscape of this town. My interest in Baines for purposes of this thesis is the manner in which he represented Grahamstown and how he was propagator of British imperialism under the guise of 'spreading civilisation' among the 'back ward' inhabitants of this continent. My painting practice is influenced by and responds to the vacant land theory especially Baines' works which were executed to present a Grahamstown as a purely British town 'emptying' it of all traces of non- British non- European dwellings or citizens. My practice brings back the layers of history that I have witnessed and the painting surface is slowly built up with water metaphorically destroying the solid structures that were built in the nineteenth century in Grahamstown. As a person who has lived through apartheid and a new dispensation in South Africa, this is reflected in my paintings with a tension between aesthetically pleasing painting styles and disturbing rough surface textures. Anselm Kiefer is the artist who has influenced my work in the manner of working he prefers and also in his tendency to look back at past periods in history.
Keywords: Uncatalogued